Candidate gene analysis in a case of congenital absence of the endometrium. Issue 1 (December 2016) - Simavli, Serap; Abreu, Ana; Kwaan, Mary; Dluhy, Robert; Yanushpolsky, Elena; Feltmate, Colleen; Cerda, Sandra; Carroll, Rona; Kaiser, Ursula; Kuohung, Wendy
Abstract Background Primary amenorrhea usually result from a genetic or anatomic abnormality. We present the first reported patient with the absence of endometrium and lumen in a small bicornuate uterus in a patient with primary amenorrhea. Case presentation A 41-year-old woman presented for evaluation of primary amenorrhea and infertility. She did develop normal secondary sexual characteristics but never had menses. Physical examination, hormone analyses, and karyotype analysis were normal. Transvaginal ultrasonography revealed a small uterus with absent endometrial stripe. Ovaries were normal in size. Pathology from hysterectomy for abnormal Pap smears revealed a hypoplastic bicornuate uterus with absence of lumen and absent endometrium. DNA analyses for mutations in the coding sequences of three members of HOXA gene family was performed, but no variants in the coding sequence of these genes were found. These findings support the hypothesis that mutations in the coding sequence of HOXA10, HOXA11, and HOXA13 are not responsible for congenital endometrial absence with bicornuate hypoplastic uterus. Conclusions Congenital absence of the endometrium is an uncommon etiology for primary amenorrhea, and nonvisualization of the endometrial stripe on ultrasound imaging in association with primary amenorrhea should raise suspicion of this rare disorder in this case.